Anti-Inflammatory Effects of Magnetically Targeted Mesenchymal Stem Cells on Laser-Induced Skin Injuries in Rats [Corrigendum] - Li X (Dove Medical Press, 2020)
Li X, Wei Z, Zhang W, et al. Int J Nanomedicine.  2020;15:5645— 5659. The authors have advised due to an error that occurred at the time of figure assembly the incorrect image was selected for the MSC group in Figure 5A on page 5654. The correct Figure 5 is shown below. The authors apologize for this error and advise it does not affect the results and conclusions of the paper. Read the original article